DECISION-MAKING MODELLING IN A BUILDING ORGANIZATION MANAGING - T. G. Aigumov; V. B. Melekhin (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The aim of the work is to develop a situational decision-making model that provides effective management of the activities of large construction engineering organisations under the unstable conditions of the economic environment.Method. The research methods are based on the application of the methodological foundations of situational management and the principles of processing expert data using the mathematical apparatus of fuzzy sets.Results. A method for managing the activities of a construction engineering organisation under an unstable economic environment is proposed. Logical-transformational rules for deriving an information-analytical model of situational management and decision support under conditions of uncertainty are developed. The necessary conditions for the effective use of various logical-transformational inference rules and the need for an organisational management transition to multi-step situational management of the construction engineering organisation are defined.Conclusion. The results of the study allow the effective management of various types of activities of a large construction engineering organisation to be carried out in an unstable economic environment (i.e. under the unstable conditions of the contemporary market).